2015
DOI: 10.1038/ncomms9113
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid transporters cooperate to control seed germination

Abstract: Seed germination is a key developmental process that has to be tightly controlled to avoid germination under unfavourable conditions. Abscisic acid (ABA) is an essential repressor of seed germination. In Arabidopsis, it has been shown that the endosperm, a single cell layer surrounding the embryo, synthesizes and continuously releases ABA towards the embryo. The mechanism of ABA transport from the endosperm to the embryo was hitherto unknown. Here we show that four AtABCG transporters act in concert to deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
222
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(228 citation statements)
references
References 63 publications
4
222
0
2
Order By: Relevance
“…This way, we accounted for Kang et al. () who reported that abscisic acid (ABA) and gibberellin (GA) status as well as environmental factors, such as light quality, temperature and water potential, may exert major effects on seed germination. Nevertheless, the presence of maternal genetic and epigenetic effects on seed germination cannot be precluded from the experiments.…”
Section: Discussionmentioning
confidence: 99%
“…This way, we accounted for Kang et al. () who reported that abscisic acid (ABA) and gibberellin (GA) status as well as environmental factors, such as light quality, temperature and water potential, may exert major effects on seed germination. Nevertheless, the presence of maternal genetic and epigenetic effects on seed germination cannot be precluded from the experiments.…”
Section: Discussionmentioning
confidence: 99%
“…ABA is a hormone that plays a vital role during the dormancy-to-germination transition (Finkelstein et al, 2002; Nambara and Marion-Poll, 2003; Chen et al, 2008; Kang et al, 2015). ABSCISIC ACID INSENSITIVE3 (ABI3) is an important transcription factor in the ABA signaling pathway (Finkelstein et al, 2008), participating in many different development stages including plastid development (Rohde et al, 2000), bud dormancy and flowering time (Rohde et al, 2002), lateral root development (Brady et al, 2003), desiccation tolerance (Khandelwal et al, 2010), and leaf development (Rohde et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] At the same time, with the rapid development of society and increase of population, plant hormones are playing an indispensable role in agriculture, such as promoting fruit ripening and leaf drop, accelerating seed germination and budding, resisting agricultural natural disaster and increasing crop yields, etc. [7][8][9][10] Plant hormones are found not only in higher plants, but also in algae, and in plant-associated bacteria and fungi. [11][12][13] However, in this case, plant hormones are not the essential small molecular necessary to the growth and reproduction of the microorganisms.…”
Section: Introductionmentioning
confidence: 99%